1999
DOI: 10.1074/jbc.274.11.6855
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence That the Proton Motive Force Inhibits Membrane Translocation of Positively Charged Residues within Membrane Proteins

Abstract: The M13 phage procoat protein requires both its signal sequence and its membrane anchor sequence in the mature part of the protein for membrane insertion. Translocation of its short acidic periplasmic loop is stimulated by the proton motive force (pmf) and does not require the Sec components. We now find that the pmf becomes increasingly important for the translocation of negatively charged residues within procoat when the hydrophobicity of the signal or membrane anchor is incrementally reduced. In contrast, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 49 publications
4
33
0
Order By: Relevance
“…For example, the residues that are involved in pH sensing were found in the cytoplasmic HAMP domain (Umemura et al, 2002), whereas residues that might control the transducer mobility in the membrane in response to changes in the electrochemical proton gradient are likely to be located in the membrane/cytoplasm interface (i.e. between the transmembrane helix and the HAMP domain), as suggested for other transmembrane proteins (Schuenemann et al, 1999). …”
Section: Discussionmentioning
confidence: 99%
“…For example, the residues that are involved in pH sensing were found in the cytoplasmic HAMP domain (Umemura et al, 2002), whereas residues that might control the transducer mobility in the membrane in response to changes in the electrochemical proton gradient are likely to be located in the membrane/cytoplasm interface (i.e. between the transmembrane helix and the HAMP domain), as suggested for other transmembrane proteins (Schuenemann et al, 1999). …”
Section: Discussionmentioning
confidence: 99%
“…To carry out this test, we examined two Procoat mutants, which previously have been shown to insert independent of the electrochemical membrane potential (26,29). We found that membrane insertion of both mutants is YidC-dependent (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3A shows that 0PCLep is inhibited under conditions in which YidC is depleted, while in the presence of YidC, 0PCLep inserts across the membrane and is processed by leader peptidase. Likewise, the potential-independent ProcoatLep mutant, PCLep (0) (29), without any charged residues in the periplasmic region was also dependent on YidC (Fig. 3B).…”
Section: Yidc Functions To Promote Membrane Insertion Of Both Membranmentioning
confidence: 99%
“…SKP1101 and SKP1102 were transformed with pINGE-Lep (Table 1) and grown as described above prior to the expression of Lep being induced with arabinose. After 2 h at the nonpermissive temperature, cells were pulse-labeled and the protease accessibility of the large periplasmic domain of Lep was measured as previously described (56).…”
Section: Methodsmentioning
confidence: 99%
“…SKP1101 and SKP1102 were transformed with pINGE-Lep (15), encoding leader peptidase (Lep) under arabinose control. Following induction of Lep synthesis at both 30 and 42°C, control and mutant cells were pulse-labeled, and the accessibility of the large periplasmic domain of Lep to protease digestion was determined (56).…”
Section: Vol 184 2002 Temperature-sensitive Ffh Mutant 2647mentioning
confidence: 99%